2023
DOI: 10.1021/acs.jafc.2c07880
|View full text |Cite
|
Sign up to set email alerts
|

Maltose-Enhanced Exopolysaccharide Synthesis of Lactiplantibacillus plantarum through CRP-like Protein

Abstract: Carbon sources alter the synthesis of exopolysaccharides (EPS) in Lactiplantibacillus plantarum. Maltose increased the EPS production of L. plantarum 163 6.5-fold. Subsequently, EPS production, transcriptome, and proteome were analyzed using glucose or maltose to further clarify the regulatory mechanism. A cAMP receptor protein (UniProtKB: F9UNI5) has been identified to control EPS synthesis in the presence of cAMP by binding to the EPS synthesis promoter Pcps4A‑J. Overexpression of the cAMP synthesis gene cya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The biological role of HoPs in Ln. strains is not sufficiently clear, though the existing hypothesis points out functions such as energy storage, environmental protection (adverse pH, desiccation, depredation), cell adhesion (oral cavity or intestinal tract), and cell communication in biofilms [14][15][16][17][18]. Moreover, despite the increasing evidence of the role of Ln.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological role of HoPs in Ln. strains is not sufficiently clear, though the existing hypothesis points out functions such as energy storage, environmental protection (adverse pH, desiccation, depredation), cell adhesion (oral cavity or intestinal tract), and cell communication in biofilms [14][15][16][17][18]. Moreover, despite the increasing evidence of the role of Ln.…”
Section: Introductionmentioning
confidence: 99%
“…mesenteroides strains demonstrated a decrease in GTFs activity when glucose or fructose are used instead of sucrose as a carbon source in aerobic cultures [21][22][23]. The presence of diverse mechanisms for the uptake of carbon sources, such as permeases and the involvement of the Phosphotransferase System (PTS) was made evident [18,23,24], and most conclusions indicated that sucrose is an atypical inducer for dextransucrase, at least in the case of Ln. mesenteroides NRRL B512F where the existence of post-transcriptional regulation was suggested [22].…”
Section: Introductionmentioning
confidence: 99%